Is Common Denominator Lead to Misdiagnosis of Dementia and Late-Life Depression - Göktaş, Seyyide Şifa (Utan Kayu Publishing, 2024)
Significant cognitive impairments are found in late life depression. This situation brings to mind the question of what are the common and distinct mechanisms of late life depression and dementia. In this review, neural and psychological mechanism are discussed within the scope of denominator and hallmark for both disorders. It is searched several databases e.g. MEDLINE, Web of Science Core Collection from 1974 to 2024 by using variant terms for the focal epilepsy subtypes and social cognition constructs. The pathology of dementia was correlated with late-life depression Studies indicate that depression may be an etiological factor for dementia as well as an increased risk. Also, many life-related stressors can lead to results such as increased reactive oxygen species, inflammatory responses, suppression of neurogenesis, and apical dendritic atrophy and altered functional connectivity in the medial prefrontal cortex. Based on this, it is possible to say that psychological stress factors increase the incidence of the disease in the development of dementia, just like in depression. Late depression should not be labeled as dementia because of they share similar symptoms and should be evaluated clinically correct so that it is not misdiagnosed. Besides, it is substantial to comprehend the relationship between the aging population and the risk of depression and dementia for current and future studies, especially in terms of prevention and treatment.